2017
DOI: 10.1002/admi.201700027
|View full text |Cite
|
Sign up to set email alerts
|

Argon Plasma Treatment of Fluorine‐Free Silane Coatings: A Facile, Environment‐Friendly Method to Prepare Durable, Superhydrophobic Fabrics

Abstract: A novel method to prepare durable superhydrophobic fabrics through pre‐applying an alkyl silane (alkyl chain longer than C15) onto fabric substrate and by subsequent vacuum plasma treatment in argon is reported. The treated fabrics show a contact angle of 154.2° with low contact angle hysteresis (sliding angle 4.5°). The coatings are durable and can withstand 150 cycles of standard laundries. The argon plasma treatment is found to significantly enhance SiOSi bonding among the silane molecules, leading to a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 41 publications
(42 reference statements)
0
32
0
Order By: Relevance
“…In our recent work, we have developed a novel method for preparing durable superhydrophobic fabrics using silane with long alkyl chain as material . We found that argon plasma could significantly stabilize silane coating and form a durable superhydrophobic layer on substrates.…”
Section: Introductionmentioning
confidence: 99%
“…In our recent work, we have developed a novel method for preparing durable superhydrophobic fabrics using silane with long alkyl chain as material . We found that argon plasma could significantly stabilize silane coating and form a durable superhydrophobic layer on substrates.…”
Section: Introductionmentioning
confidence: 99%
“…3c , the characteristic peaks of the coating before modification were observed at 916 cm −1 for the -CH(O)CH- groups of ER, 1095 cm −1 for the Si-O-Si groups of SiO 2 and 1646 cm −1 for the C=O groups of polyamide (PA) 54 . In addition, after modification, the Si-O-Si (1095 cm −1 ), -CH2- (2850 cm −1 ) and -CH3 (2920 cm −1 ) stretching vibrations became stronger than those in the unmodified coating, thereby demonstrating that the coating was successfully modified with DTMS 42 , 55 .
Figure 3 Chemical compositions of the coatings.
…”
Section: Resultsmentioning
confidence: 97%
“…However, fluoro-containing compounds are expensive and harmful to the environment and human health 39 41 . Therefore, fluorine-free compounds that are inexpensive and environmentally friendly, such as alkyl silanes and long carbon chain organics, have been developed for the fabrication of superhydrophobic surfaces 42 44 . Furthermore, noxious organic solvents are often used to prepare coating suspensions during the fabrication of superhydrophobic surfaces, which is environmentally hazardous.…”
Section: Introductionmentioning
confidence: 99%
“…Stability in the refractive index of the APSs is dependent on the wettability of the liquids on APSs. According to current reports [32,33], the combination of surface roughness and low-surface-energy materials is responsible for wettability. Through the alkylated and fluorinated modification, low-surface-energy was successfully endowed for SiO 2 nanospheres.…”
Section: Resultsmentioning
confidence: 99%